KAJIAN MANAJEMEN RISIKO UNTUK EVALUASI EKONOMI PEMBUKAAN PROYEK BATUBARA - Laura Puspita Sari, (ReTII, 2019)
Opening a coal mining project poses external and internal risks. External risk consists of commodity price risk and regulatory risk, while internal risk consists of financial risk and operational risk. The purpose of this study is to analyze risk treatment by taking into account the influence of external and internal factors so that the project is feasible to be mined. Research methods include risk identification, risk analysis, risk evaluation and risk treatment used to prove the feasibility of a mine. The study in this study is a coal mining company in the area of ​​East Kalimantan Province. Expansion of the area of ​​34.78 Ha at the mine surface. Mine planning is based on consideration of the potential of coal reserves is 473,630 tons, coal quality is 5,790 kcal and total overburden is 10,407,600 bcm. Based on overburden density is 2.25 tons / bcm, the stripping ratio is 25: 1. The results of the study prove that the analysis using efforts to reduce costs can increase the feasibility of the mine to be developed.